Development and Validation of An Instrument for Determining Knowledge and Practice of Pistachio Farmers in Terms of Aflatoxin and the Prevention Methods of its Production in Pistachio Product - parvaneh yekzamani; azadeh ashtarinezhad; tahereh dehdari; batol masruri; Jamileh Abolghasemi (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: Given the necessity of assessing knowledge and practice of individuals to prevent the Aflatoxin contamination in pistachio in order to develop appropriate educational interventions, design and validating a standard tool is essential. Therefore, the purpose of this study was to develop and validate an instrument to determine the knowledge and performance of pistachio farmer in terms of Aflatoxin contamination and the methods to prevent its production in pistachio product. Methods: In this research, initial items of instrument were designed based on literature review and interview with experts and farmers. The face validity, Content Validity Ratio (CVR) and Content validity Index (CVI) of instrument were determined by interview with farmers and through opinions of experts' panel respectively. Test-retest analysis was conducted to test the stability of the instrument. Also, according to the data of 380 farmers, exploratory factor analysis (EFA) was performed. Results: The results showed that CVI and CVR of items of instrument were ≤0.79 and ≤0.62 respectively. Confirmatory factor analysis indicated a good fit for the data. EFA Analysis showed that KMO is suitable for 3 groups of Knowledge and also for practice. Bartlett's test was significant and zero hypothesis of data was rejected. According to factor load higher than 0.3 for every question, neither of them was removed. Finally, questionnaire of Knowledge was confirmed with 18 and Practice questionnaire was confirmed with 10 questions. Conclusion: The developed instrument can be used to measure the knowledge and practice of pistachio farmers about Aflatoxin contamination, as a research tool, to be used to develop appropriate educational interventions.